Bhutan Investment Climate Assessment Report : Vitalizing the Private Sector, Creating Jobs, Volume 1. Summary Report - World Bank (Washington, DC, 2013)
The objective of the Bhutan Investment Climate Assessment (ICA) is to evaluate the investment climate in Bhutan in all its operational dimensions and promote policies to strengthen the private sector. This ICA consists of two volumes. Volume 1 summarizes the main results. Volume 2 presents a more detailed analysis of each of the three main themes of the report: labor productivity and skills, access to finance, and business government relations, and is supplemented by a chapter on the gender dimensions of the investment climate. Volume 2 also includes the supporting econometric analysis of the enterprise survey data. The purpose of Volume 2 is to provide additional detail on the underlying data and analysis which supports the main results summarized in Volume 1. In Volume 2, Chapter 1 sets the Bhutanese context and background, explains what's new in the second Bhutan Investment Climate Assessment, and presents the overall findings of the 2010 report. Chapter 2 reviews the characteristics of the investment climate in Bhutan, including the macroeconomic perspective. Chapter 3 discusses labor productivity and skills and the importance of focusing on high value added niche industries. Chapter 4 reviews access to finance as a primary constraint to firms in Bhutan and discusses an apparent access to finance paradox. Chapter 5 reviews the business government enabling environment in Bhutan and the importance of licensing reform. Chapter 6 discusses the gender dimension of the investment climate in Bhutan.